Metabolic Responses of Subtropical Microplankton After a Simulated Deep-Water Upwelling Event Suggest a Possible Dominance of Mixotrophy Under Increasing CO2 Levels - Tames-Espinosa, Mayte; Martínez, Ico; Romero-Kutzner, Vanesa; Coca, Josep; Algueró-Muñiz, María; Horn, Henriette G.; Ludwig, Andrea; Taucher, Jan; Bach, Lennart; Riebesell, Ulf; Packard, Theodore T.; Gómez, May (Frontiers in Marine Science, 2020)
In the autumn of 2014, nine large mesocosms were deployed in the oligotrophic subtropical North-Atlantic coastal waters off Gran Canaria (Spain). Their deployment was designed to address the acidification effects from 400μatm CO2 to 1400μatm CO2, on a plankton community experiencing upwelling of nutrient-rich deep water. Among other parameters, chlorophyll a (chl-a), potential respiration (Φ), and proteinaceous biomass (B) were measured in the microplankton community (0.7-50 μm) during an oligotrophic phase (Phase I), a phytoplankton-bloom phase (Phase II) and a post-bloom phase (Phase III). Here, we explore the use of the Φ/chl-a ratio in monitoring shifts in the microplankton community composition and its metabolism. Φ/chl-a values below 2.5μLO2h−1(μgchl-a)−1 indicated a community dominated by photoautotrophs. When Φ/chl-a ranged higher, between 2.5-7μLO2h−1(μgchl-a)−1, it indicated a mixed community of phytoplankton, microzooplankton, and heterotrophic prokaryotes. When Φ/chl-a rose above 7μLO2h−1(μgchl-a)−1, it indicated a community where microzooplankton proliferated (>10μLO2h−1(μg chl-a)−1), because heterotrophic dinoflagellates bloomed. The first derivative of B, as a function of time (dB/dt), indicates the rate of protein build-up when positive and the rate of protein loss, when negative. It revealed that the maximum increase in particulate protein (biomass) occurred between one and two days before the chl-a peak. A day after this peak, the trough revealed the maximum net biomass loss. This analysis did not detect significant changes in particulate protein, neither in Phase I nor in Phase III. Integral analysis of Φ, chl-a and B, over the duration of each phase, for each mesocosm, reflected a positive relationship between Φ and pCO2 during Phase II (α=230 10-5 μLO2h−1L−1 (μatmCO2)−1(phase-day)−1, R2=0.3009) and between chl-a and pCO2 during Phase III (α=100 10-5 μg chl-aL−1(μ atmCO2)−1 (phase-day)−1, R2=0.8444). At the end of Phase II, a harmful algal species (HAS), Vicicitus globosus, bloomed in the high pCO2 mesocosms. In these mesocosms, microzooplankton did not proliferate, and chl-a retention time in the water column increased. In these V. globosus-disrupted communities, the Φ/chl-a ratio (4.1±1.5μLO2h−1(μg chl-a)−1) was similar to the Φ/chl-a ratio in a mixed plankton community than to a photoautotroph-dominated one.